Genotypic Differences Affecting Biometric, Processing and Functional Quality Attributes in Tomato Fruits - Yors Laayouni; Ilahy Riadh; Imen Tlili; Ahlem Ben Ali; Thouraya R'him (Turkish Journal of Agriculture: Food Science and Technology)
Processing tomato is an important agricultural crop worldwide suffering from genetic erosion due to a severe genetic diversity reduction and domestication hindrance. In Tunisia, some old underutilized tomato cultivars are increasingly being considered as genetic resources and are marginally used by small farmers constituting a real safety valve for the sustainability of the processing tomato value chain. Those tomato cultivars differ in their biometric, processing and functional quality attributes. Therefore, there is an increasing interest to examine their performances for processing and fresh market quality improvement. Recently, there was also a particular focus on improving the quality of fresh fruit via the introgression of high-pigment genes in processing tomato in order to obtain a high quality processed products. The results are important as large differences are highlighted and the main traits affecting tomato quality are also reported and clearly discussed. This suggest that maintaining of the existing genetic pools among cultivated tomato is as important as creating novel hybrids.